2015
DOI: 10.1167/iovs.14-15503
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Ganglion Cell Layer Thinning and Poor Visual Function After Resolution of Diabetic Macular Edema

Abstract: Despite favorable anatomic response and restoration of a CMT in the range of normal values after resolution of DME, the GCIPL thickness in r-DME eyes was lower than that in no-DME eyes and correlated with the VA. These results suggest that inner retinal alterations occurring in patients with DME and diabetic retinopathy may lead to visual deficiency persisting after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 15 publications
(16 reference statements)
5
52
3
Order By: Relevance
“…Furthermore, early 4-month change in DRIL extent predicted VA change from baseline to 1 year 44. Coinciding with this data is a publication by Bonnin et al ,45 which showed that despite favourable anatomic response, a thin ganglion cell-inner plexiform layer was associated with lower visual acuity despite normal thickness. This again suggests that inner retinal alterations occurring in DME would seem to strongly affect visual outcomes.…”
Section: Defining Responsesupporting
confidence: 54%
“…Furthermore, early 4-month change in DRIL extent predicted VA change from baseline to 1 year 44. Coinciding with this data is a publication by Bonnin et al ,45 which showed that despite favourable anatomic response, a thin ganglion cell-inner plexiform layer was associated with lower visual acuity despite normal thickness. This again suggests that inner retinal alterations occurring in DME would seem to strongly affect visual outcomes.…”
Section: Defining Responsesupporting
confidence: 54%
“…Other OCT studies reveal that in cases of diabetic macular edema associated with disorganization of the inner retinal layers, visual acuity improvement was related to restoration of the normal retinal layering (Radwan et al, 2015). Similar results were noted with regard to thickness of the ganglion cell layer, irrespective of the CRT (Bonnin et al, 2015). These studies suggest that while CRT is an important factor in the response to treatment and visual restoration, specific patterns of macular edema as well as restoration of normal retinal architecture are also important factors.…”
Section: Pathophysiology Of Diabetic Macular Edemasupporting
confidence: 67%
“…RDN is clinically relevant, for example affecting the visual outcome after successful treatment of diabetic macular edema (26). Retinal neurodegeneration at the cellular and functional (ERG) level has been described previously (27) in another mouse model of spontaneous DM.…”
Section: Discussionmentioning
confidence: 90%